USE OF PARALLEL AND FACET ASSIGNMENTS IN THE SYSTEM OF DISTANT LEARNING “MOODLE” - Anatoly A. Yerofeyev; Oleg A. Sychev (Открытое образование (Москва), 2016)
The paper describes features and advantages of parallel and facet tests and tasks, their implementation in various popular learning management systems. Principles of functioning and advantages of developed module for LMS Moodle are described. The developed module implements facet approach and allows further development.